Wildrock : empowering social connection and play in Virginia’s Blue Ridge region - Mulloth, Bala, (SAGE Business cases., 2024)
In this case, we study the growth, evolution, and impact of Wildrock, a nonprofit organization that is helping improve the mental health and happiness of people in and around Charlottesville, Virginia, through access to nature and nature play. Wildrock was created by Carolyn Schuyler, a licensed clinical social worker, in response to increasing mental illness among young adults and a decrease in outdoor play among children. Wildrock's mission is to promote nature play for health and happiness. They achieve this mission primarily through their outdoor playscape in the Blue Ridge foothills of central Virginia and pop-up play installations in underused urban green spaces. By making space for nature play and reinvigorating positive mental health practices, Wildrock has set itself apart as a viable model for how entrepreneurs may drive grassroots movements by developing innovative solutions to societal challenges. In addition to investigating the Wildrock social impact and business model, students will assess the various strategic decisions and challenges Wildrock faces as they seek to maximize impact in the years ahead. Students will analyze Wildrock's tradeoffs between expanding to serve additional constituents and focusing efforts on securing financial stability in their current state.